O cuidador de paciente com neoplasia cerebral maligna primária: os desafios do cuidado - Prado, Gabriela da Matta (2014)
Patients with primary malignant brain tumor endure several motor and cognitive dysfunctions, demanding the presence of a caregiver even more because the time necessary for their assistance increases considerably. Usually this task is performed by a family relative, whose activities include taking care of the patient’s personal hygiene, escorting them to medical appointments, managing their money and performing their housework. All of this overwhelms the caregiver both physical and psychologically. This bibliographic research intends to analyze the role in which a caregiver plays in the quality of life of those kinds of patients, the complications of such task, the caregivers’ needs and the daily life of those terminal patients. It was used CAPES, PubMed and Google Academic databases for researching articles related to family caregivers who assisted adult patients with primary malignant brain tumor. The study concluded that being a caregiver of patients in such conditions harms one’s quality of life, with consequences such as stress, insomnia, financial problems and lack of social support. Theirs needs include: having someone to talk to about the matter, attending programs for reducing stress and increasing their knowledge about the disease. In advanced phases of the condition, the patient shows great mobility problems, aphasia and regular seizures, which end up overwhelming the caregiver. The level of quality of life found was above other types of cancer’s caregivers. Therefore, they represent a group with special needs, which should be especially handled by health professionals.